2014
DOI: 10.1002/ijc.29103
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of AKT expression by miR‐153 produced anti‐tumor activity in lung cancer

Abstract: Lung cancer is one of the leading causes of cancer death worldwide. microRNAs have been shown to be a novel class of regulators in lung cancer. Here, we explored the role of miR-153 in the pathogenesis of lung cancer and its therapeutic potential. miR-153 was significantly decreased in lung cancer tissues than the adjacent tissues. The protein and mRNA levels of protein kinase B (AKT), which were shown to promote tumor growth, were both increased in lung cancer tissues than adjacent tissues. Overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 24 publications
0
37
2
Order By: Relevance
“…Knockdown of AKT expression suppressed lung cancer cell proliferation [28], and the molecules correlated with apoptosis such as Bcl-2 and caspase-3 are the downstream targets of Akt [29]. In this study, B7-H4 gene silencing induced by B7-H4 shRNA inhibited AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 68%
“…Knockdown of AKT expression suppressed lung cancer cell proliferation [28], and the molecules correlated with apoptosis such as Bcl-2 and caspase-3 are the downstream targets of Akt [29]. In this study, B7-H4 gene silencing induced by B7-H4 shRNA inhibited AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 68%
“…14,15 MicroRNAs, such as miR-494, miR-153 and miR-218, inhibited lung cancer development and metastasis via suppressing cellular proliferation, inhibiting cell migration and invasion and EMT. [16][17][18] Here, we found that B3GNT3 was overexpressed in lung cancer and upregulated expression of B3GNT3 was associated with unfavorable prognosis of lung cancer patients. Silencing B3GNT3 inhibited lung cancer cell growth in vitro and suppressed lung tumor development in vivo.…”
Section: Introductionmentioning
confidence: 70%
“…Moreover, mir‐486 was reported to be cytotoxic in A549 LUAD cells by repressing the expression of bone morphogenetic protein‐2 reporter gene . Hsa‐mir‐153 was found to be down‐regulated in NSCLC tissues and cell lines; it inhibits migration and invasion of NSCLC by targeting ADAM19 and protein kinase B ( AKT ) . These three miRNAs were speculated to serve as tumor suppressors in LUAD.…”
Section: Discussionmentioning
confidence: 99%